The Impact of Work Environment on Nursing Students’ Choices of Employer : A Qualitative Study on Recruitment of Nurses to Municipal Health Care Services - Gundersen, Ellen Dahl; Jentoft, Nina; Svensson , Odd Joar; Hellang, Øyvind (Nordisk Tidsskrift for Helseforskning, 2023)
There is an increasing demand for nurses in municipal health care services. A survey among third-year students from a cohort in a bachelor’s program in nursing (n=101) highlighted work environment as the most important factor when choosing an employer as newly qualified nurses. This article presents a follow-up study where the purpose was to gain increased insight into what nursing students associate with a good work environment. The study had a qualitative design, with semi-structured interviews from 15 students recruited from the same cohort as the survey. The interview data was analyzed thematically. The students described a good work environment as exciting, supportive, and livable. The results indicate that the facilitation of a good work environment for nursing students during their practical studies, as well as for newly qualified nurses, can have an impact on recruitment to municipal health care services.